THE ROLE OF MOTHERS REGARDING BEHAVIOR IN DENTAL HEALTH IN RELATION TO CONSUMING BETEL NUT IN LOW INCOME COMMUNITY EARLY EDUCATION CHILDREN IN KUPANG REGENCY INDONESIA - Christina Ngadilah; Leni Marlina Pinat SST, MKes; Merniwati Sherly Eluama S.Kp.G, MDSc; Ardent Kloee Titu Eki STH, MSW (Green Publisher, 2023)
This research is based on the aim of identifying socio-cultural values ??in the health sector regarding dental health in consuming betel areca in parents whose children attend PAUD, as well as revealing the role of mothers in strengthening culture, especially the culture of consuming betel nut, which is appropriate for low-income communities in rural areas of Kupang Regency. The Aim of the research to analisa The role of the mothers regarding behavior in dental health in relation to consuming betel nut in low income community Early Education children.Method: This research is a quantitative and qualitative research. Mothers who have children under the age of five whose children attend PAUD intervention by UNISEF in the last 5 years. Respondents include parents and PAUD children in 5 regions representing the District . Kupang is District. Takari, Amfoang, Semau Amarasi and Fatuleu. Data collection methods include questionnaire interviews with mothers with children aged 3-5 years in each district analyzed. The selection for Low-Income Communities is people who receive BLT from the village. Result of this research is a model of the role of mothers in maximizing children's growth and development in areas that are claimed to be low in Kupang Regency. According to research, mothers must be experienced in dental health and betel nut because they are the ones who understand best, the main caregivers for their children and in this area most children consume betel nut which is dangerous for oral health and body health in general. Conclusion: Most mothers in the research area adhere to culture and customs and teach their children from an early age about consuming betel nut. Suggestion: To improve children's dental and oral health, it is very important to increase mothers' knowledge through socialization about dental health and the dangers of areca nut for general health